2021
DOI: 10.3389/fmars.2021.713991
|View full text |Cite
|
Sign up to set email alerts
|

Poleward Propagation of Typhoon-Induced Near-Inertial Waves in the Northern South China Sea

Abstract: One of the main responses of the ocean to typhoons is the generation of near-inertial waves (NIWs), whose intrinsic frequency is close to the local inertial frequency. Based on the mooring observations, we carefully investigated the spatial–temporal variations in NIWs in the northern South China Sea (SCS) after Typhoon “Haima,” which passed through the northern SCS from October 20 to 21, 2016, with its track parallel to the mooring array on its northeast side. Moorings in different locations responded differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Based on turning-point theory and a numerical model, Fu (1981) suggested that the observed local inertial peak over smooth topography could be interpreted in terms of poleward-propagating waves generated at lower latitudes. The poleward propagation of NIWs can also be caused by the background flow (e.g., Huang et al, 2021;Jeon et al, 2019;Tort & Winters, 2018). Tort and Winters (2018) demonstrated a scale selection mechanism by which the super-inertial component of NIWs is able to propagate poleward over long distances in the presence of mesoscale turbulence with horizontal scales considerably smaller than the width of the storm track.…”
mentioning
confidence: 99%
“…Based on turning-point theory and a numerical model, Fu (1981) suggested that the observed local inertial peak over smooth topography could be interpreted in terms of poleward-propagating waves generated at lower latitudes. The poleward propagation of NIWs can also be caused by the background flow (e.g., Huang et al, 2021;Jeon et al, 2019;Tort & Winters, 2018). Tort and Winters (2018) demonstrated a scale selection mechanism by which the super-inertial component of NIWs is able to propagate poleward over long distances in the presence of mesoscale turbulence with horizontal scales considerably smaller than the width of the storm track.…”
mentioning
confidence: 99%
“…Decompose the near-inertial currents of HYCOM into vertical modes from 0 to 800 m, and perform a depth integration for different modes (Figures 10,11). Examples of applying this method to the range from the surface to the maximum depth that NIWs can reach were common in previous work (Chen et al, 2013;Hou et al, 2019;Huang et al, 2021), so the range of 0-800 m selected for this study is fairly reasonable.…”
Section: Mode Structurementioning
confidence: 99%
“…The subtropical northwest Pacific has complex multiscale oceanic dynamic processes and is also characterized by an abundance of TCs (Hu et al, 2020). Due to the difficulty of implementing marine observations, most previous studies have focused on the South China Sea (Huang et al, 2021;Yang et al, 2021), and research on NIWs east of Taiwan, where mesoscale processes are highly active, remains limited. In this paper, by comparing observations with HYCOM data, we confirmed that HYCOM data can effectively simulate the typhoon-generated NIWs east of Taiwan during Typhoon MITAG.…”
mentioning
confidence: 99%
“…Based on turning-point theory and a numerical model, Fu (1981) suggested that the observed local inertial peak over smooth topography could be interpreted in terms of poleward-propagating waves generated at lower latitudes. The poleward propagation of NIWs can also be caused by the background flow (e.g., Tort & Winters, 2018;Jeon et al, 2019;Huang et al, 2021). Tort and Winters (2018) demonstrated a scale selection mechanism by which the super-inertial component of NIWs is able to propagate poleward over long distances in the presence of mesoscale turbulence with horizontal scales considerably smaller than the width of the storm track.…”
Section: Introductionmentioning
confidence: 99%